2023
DOI: 10.1002/advs.202304891
|View full text |Cite
|
Sign up to set email alerts
|

A Bacterial Quorum Sensing Regulated Protease Inhibits Host Immune Responses by Cleaving Death Domains of Innate Immune Adaptors

Xiangke Duan,
Zhao Zhi Boo,
Song Lin Chua
et al.

Abstract: Innate immune adaptor proteins are critical components of the innate immune system that propagate pro‐inflammatory responses from their upstream receptors, and lead to pathogen clearance from the host. Bacterial pathogens have developed strategies to survive inside host cells without triggering the innate immune surveillance in ways that are still not fully understood. Here, it is reported that Pseudomonas aeruginosa induces its quorum sensing mechanism after macrophage engulfment. Further investigation of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…The results showed that the ΔpqsS mutant developed 2.37-fold and 2.26-fold increased antibiotic-tolerant subpopulations in response to colistin treatment compared to the PAO1 WT and ΔpqsS+ strains, respectively (Figure 3C, 3D). Chronic infection of P. aeruginosa is associated with its ability to resist immune clearance and survive inside phagocytic cells 36 . Therefore, we investigated whether PqsS will affect the phagocytosis rate and intracellular survival of PAO1 by using the RAW264.7 macrophage infection assay.…”
Section: Pqss Reduces Pao1 Chronic Infection Traits Including Biofilm...mentioning
confidence: 99%
“…The results showed that the ΔpqsS mutant developed 2.37-fold and 2.26-fold increased antibiotic-tolerant subpopulations in response to colistin treatment compared to the PAO1 WT and ΔpqsS+ strains, respectively (Figure 3C, 3D). Chronic infection of P. aeruginosa is associated with its ability to resist immune clearance and survive inside phagocytic cells 36 . Therefore, we investigated whether PqsS will affect the phagocytosis rate and intracellular survival of PAO1 by using the RAW264.7 macrophage infection assay.…”
Section: Pqss Reduces Pao1 Chronic Infection Traits Including Biofilm...mentioning
confidence: 99%